ENDRIN INDUCED HEPATIC INJURY IN CHANNA PUNCIATUS (HAM.) - Sastry, K V; Sharma, S K (Indian Journal of Fisheries, 2011)
Ths effffect of a sublethal concentration (0.01 mg/1) of endrin on thehistological chrnges in the liver of a ^^leost fish, Channa punctatus (Ham.) has beenstudied. The degenerative changes included hype^rtrophy of hepEtic cells and theirnuclei, liver cord disarray, vacuolation of cytoplasm and necrosis. In some cells,the cell membrane was ruptured. The centrolobular area was highly necrosed. Theliver on the whole showed distorted appearance